Artificial rabbit vagina prototype through 3D innovationin meat production - Carhuachin Marcelo, Betsy Jazmín (2024)
The objective of the study was to examine the impact of a3D printed artificial vagina for the production and industryof rabbit meat in Huaral -Lima. Developed in the DigitalFabrication Laboratory of the Instituto de Educación SuperiorTecnológico Público “Huando”. It begins with theanalysis of the current situation of the rabbit meat market,highlighting its importance in gastronomic tourism and theconstant demand in country restaurants. Artificial vagina ispresented as an innovative tool to improve the reproductiveefficiency of rabbits, promoting sustainability and competitiveness.The business model focuses on the production andcommercialization of these artificial vaginas aimed at breed-ers. The value proposition highlights improved efficiency,cost reduction through the use of PLA, and environmentalsustainability. The impact analysis anticipates improvementsin production, technological development, sustainable practicesand employment generation, supported by a cost analysis.The linkage to sustainable development goals underlinesthe contribution in the fight against hunger, job promotion,livestock innovation and infrastructure, responsible productionand consumption, and climate action. It is concludedthat 3D printed artificial vagina not only offers a technologicaldevelopment, but also positions itself as an integraldriver of sustainable development in livestock production.